ATTITUDES TOWARD AGING AMONG GRADUATE STUDENTS FROM DIFFERENT MEDICAL AREAS. (16th November 2018) - Jester, D; Andel, R; Hyer, K
Abstract: Geriatric education remains a crucial area in providing quality of care to older adults. Attitudes toward older adults may play an important role in how students respond to geriatric education and practice. We explored perceptions of older adults among medical, pharmacy, nursing, and physical therapy graduate students using the Images of Aging Questionnaire (Levy, Kasl, & Gill, 2004), an 18-item instrument asking respondents to rate their perceptions of older adults across words like healthy, wrinkled, active, senile, etc. Data were collected once per semester across four semesters (Spring 2017- Spring 2018) on 695 students while the Geriatric Workforce Enhancement Program (GWEP) was being implemented. Overall, scores for positive images were significantly higher, and scores for negative items were significantly lower, for nursing and physical therapy students compared to medical and pharmacy students (p's<.05). Highest scores were found for positive perceptions of "wise" and "family-oriented, " but also negative perceptions of "wrinkled" and "walks slowly." Over the four semesters of GWEP implementation, students were increasingly more likely to perceive older adults in a positive way and less likely to perceive them in a negative way. These trends were driven by increased scores for "healthy, " "capable, " and "active" and decreased scores for "dying" and "walking slowly" (p's<.05), with several other items showing no change. These results provide unique, novel insights into the perceptions of older adults among students from medical fields. The results can provide a platform for improving approaches toward geriatric care education among students across medical disciplines.